Long Range RFID Based Automatic Doorstops in Housing - Habibi Ramdani Safitri; Muhammad Habib Maulana (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2023)
Currently Internet of Things (IoT)-based technology is one of the new trends in the world which will most likely become a trend in the future. Simply put, IoT connects devices continuously connected to the Internet and can be controlled remotely through a user's device. The Internet of Things (IoT) is a structure where objects and people are given exclusive identities and the ability to relocate data over a network without requiring two-way touch between humans for example source to destination or human-to-computer interaction.